The pulse effect on the isolation device optimization of simply supported bridges in near-fault regions - Jiang, Linwei; Zhong, Jian; Yuan, Wancheng (Structures (Oxford), 2020)
Seismic isolation devices serve as an important measure to reduce hazards or mitigate structure damage subject to earthquakes. It’s of great necessity to select the optimal parameters of isolation devices to achieve a good performance especially for structures near the fault. In this paper, a risk-based approach is proposed to identify the optimal parameters of isolation devices particularly considering the pulse effect. The seismic risk is convolved combining the near-fault seismic hazard and seismic fragility results. Seismic hazard analysis is performed for the selected IM and seismic fragility analysis is conducted using the probabilistic seismic demand anaylsis (PSDA) method for ordinary bridges which are common in transportation networks with a set of far-field ground motions and a set of pulse-like ground motions. The objective parameters include the elastic stiffness (K1), characteristic strength (Q) and post-yielding stiffness (K2) to model the seismic behavior of isolation devies subject to ground motions. Especially, the damage criteria of piers and isolation devices are combined to derive the system-level damage of bridges. The results shows that the damage probability of isolated bridges is significantly influenced by the mechanical properties of isolation devices and pulse effect. With the discrete seismic risk points, Kriging interpolation method is used to obtain the object functions which describe the relationship between the near-fault risk and the parameters of isolation devices. With the help of optimization index, the optimal parameters of isolation devices are identified as a function of structural properties and damage states. Additionally, the pulse effect on the optimal parameters of isolation devices is quantified and the relationship between the optimized results and the source-to-site distance is established. The result can provide effective and practical guidance for design and retrofitting of near-field bridges.